The crossing : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Lincoln lawyer novel., 2016)
"Detective Harry Bosch has retired from the LAPD, but his half-brother, defense attorney Mickey Haller, needs his help. The murder rap against his client seems ironclad, but Mickey is sure it's a setup. Though it goes against all his instincts, Bosch takes the case. With the secret help of his former LAPD partner Lucia Soto, he turns the investigation inside the police department. But as Bosch gets closer to discovering the truth, he makes himself a target"--